2008
DOI: 10.1021/pr800217q
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Complex Polyubiquitin Chains to WRNIP1

Abstract: Werner helicase interacting protein 1 (WRNIP1) is a ubiquitin-binding protein that undergoes extensive post-translational modification including ubiquitination, sumoylation, and phosphorylation. These post-translational modifications are expected to regulate the function of WRNIP1 in the DNA damage response. In this study, we use a denaturing tandem affinity purification technique along with mass spectrometry to show that, unlike most ubiquitin-binding proteins, WRNIP1 is polyubiquitinated. WRNIP1 polyubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
2
23
0
1
Order By: Relevance
“…43,44 The WHIP rim staining is not as prominent as the classic MAb 414 staining, but is detectable, as seen in a previous study of WHIP by Mano 38 and consistent with our earlier discovery of WHIP's observed separate pools of polyubiquitinated and sumoylated WHIP to exist in the cell. 43,44 The modifications of WHIP most likely regulate interaction, localization and function. These pools have consequences in the location and diverse functions of WHIP.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…43,44 The WHIP rim staining is not as prominent as the classic MAb 414 staining, but is detectable, as seen in a previous study of WHIP by Mano 38 and consistent with our earlier discovery of WHIP's observed separate pools of polyubiquitinated and sumoylated WHIP to exist in the cell. 43,44 The modifications of WHIP most likely regulate interaction, localization and function. These pools have consequences in the location and diverse functions of WHIP.…”
Section: Resultssupporting
confidence: 88%
“…WHIP is highly modified; it has been found to be a target of phosphorylation, sumoylation and polyubiquitination. 32,43,44 These findings suggest that only the higher MW form is associated at the NE and the lower MW form is localized to the NP.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…We digested and processed the bands for analysis as described previously (2). We analyzed the tryptic peptides either by liquid chromatography (LC)-tandem MS (MS/MS) on a linear trap quadrupole mass spectrometer (Thermo) or by targeted fragmentation on a matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) spectrometer (Applied Biosystems) (8). We analyzed the LC-MS/MS runs using the X!Tandem search engine (19) with the following parameters: variable modifications included mono-, di-, and trimethylation of Lys and mono-or dimethylation of Arg residues.…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%